2017
DOI: 10.1002/ejoc.201601518
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐Catalyzed Photochemical C–H Arylation of Heteroarenes

Abstract: Organic dyes are a promising class of photoredox catalysts and offer a meaningful alternative to broadly applied Ru and Ir complexes. We found that porphyrins with tuned physicochemical properties, by tailoring various substituents at the periphery of the macrocycle, are effective in catalyzing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 39 publications
1
44
0
2
Order By: Relevance
“…Organic dyes are a promising class of photoredox catalysts and offer a meaningful alternative to broadly applied Ru and Ir complexes. Recently, Gryko and co‐workers found that porphyrins, with physicochemical properties tuned by tailoring various substituents at the periphery of the macrocycle, are effective in catalyzing the light‐induced direct arylation of heteroarenes and coumarins with diazonium salts. Under the optimal reaction conditions, the reactions gave moderate to good yields for the arylation of heteroarenes with diazonium salts and different functional groups were well tolerated (Scheme ).…”
Section: C(sp2)−h Bond Functionalizationmentioning
confidence: 99%
“…Organic dyes are a promising class of photoredox catalysts and offer a meaningful alternative to broadly applied Ru and Ir complexes. Recently, Gryko and co‐workers found that porphyrins, with physicochemical properties tuned by tailoring various substituents at the periphery of the macrocycle, are effective in catalyzing the light‐induced direct arylation of heteroarenes and coumarins with diazonium salts. Under the optimal reaction conditions, the reactions gave moderate to good yields for the arylation of heteroarenes with diazonium salts and different functional groups were well tolerated (Scheme ).…”
Section: C(sp2)−h Bond Functionalizationmentioning
confidence: 99%
“…The copper‐catalyzed version of this transformation (the Meerwein arylation) has been known since the 1930s, but it suffers from some important drawbacks, such as the usually low yields and the high catalyst loading required . Since then, many variations of the original procedure have been reported (Scheme ), involving both thermal and photochemical reaction conditions . König and co‐workers proved that this transformation can be photocatalyzed by eosin Y,[22a] and that under visible light irradiation the phenyl radical is formed from diazonium salt 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in contrast to solution-based methods, reactions by milling do not suffer from solubility restrictions due to the possibility to bring reactants and catalysts of very different solubility, into close proximity for achieving chemical reactivity. This last aspect is foreseen as highly valuable in transformations using low-soluble PCs (e.g., porphyrins) [ 16 ] or during the photochemical synthesis or modification of polymers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%